2021
DOI: 10.20885/ejem.vol13.iss2.art8
|View full text |Cite
|
Sign up to set email alerts
|

Export diversification and economic growth: A threshold regression approach for emerging markets and developing countries

Abstract: Purpose ─ This study investigates the nonlinear relationship between export diversification and economic growth in 44 emerging markets and developing countries.Methods ─ The threshold regression methodology is employed to analyze data for the period between 1995 and 2015. Export diversifications in terms of both geography and product are measured by the Herfindahl-Hirschman market concentration index and overall Theil index, respectively.Findings ─ The results demonstrate a nonlinear relationship between expor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Naude and Rossouw (2010) align with the studies mentioned above and reinforce the results that were found by Markakkaran and Sridharan (2022) and those suggested by Trinh and Thuy (2021) and Aditya and Acharyya (2011). Naude and Rossouw (2010) look at the relationship between export diversity and economic performance in Brazil, China, India, and South Africa (BCIS).…”
Section: Benefits Of Export Diversificationsupporting
confidence: 68%
See 1 more Smart Citation
“…Naude and Rossouw (2010) align with the studies mentioned above and reinforce the results that were found by Markakkaran and Sridharan (2022) and those suggested by Trinh and Thuy (2021) and Aditya and Acharyya (2011). Naude and Rossouw (2010) look at the relationship between export diversity and economic performance in Brazil, China, India, and South Africa (BCIS).…”
Section: Benefits Of Export Diversificationsupporting
confidence: 68%
“…They find that lower income countries benefit from export diversification, while higher income countries benefit from export specialization. Trinh and Thuy (2021) also investigate the 'non-linear' relationship between export diversification and economic growth. Although their threshold regression approach is confusing, their high-level findings communicate that export diversification can reach a level where it no longer contributes positively to economic growth.…”
Section: Benefits Of Export Diversificationmentioning
confidence: 99%
“…Schott (2008) explored export sophistication of China, USA, and other OECD members by applying a comparative approach, while Wang and Wei (2008) investigated the main determinants of China's export sophistication improvements. Additionally, Al-Marhubi (2010) presented empirical evidence that export diversification promotes economic growth for a group of selected developing countries, while Trinh and Thuy (2021) empirically investigated the non-linear relationship between export diversification and economic growth in 44 emerging markets and developing economies, supporting the thesis that export is important for long-term economic growth. Yuni, Urama, Ugwuegbe, and Agbanike (2020) examined the relationship between the level of export diversification and economic growth by applying fixed effect and GLS regression models to Sub-Saharan African countries and found a U-shaped relationship between export concentration and economic growth.…”
Section: Introductionmentioning
confidence: 86%
“…In line with the notion of immiserizing growth, economic growth countered by decreasing trade terms can exacerbate a country's situation. Developing countries become trapped in this predicament when they focus on the exportation of raw materials at a lower price relative to manufactured items (Trinh and Thuy, 2021). Sustained growth requires developing nations to diversify their exports from basic products to manufactured goods, as suggested by the term "vertical diversification."…”
Section: Literature Reviewmentioning
confidence: 99%
“…In likewise manner, Prebisch (1950) and Sachs & Waner (1995) noted that the 'natural resource curse' argument suggests that a substantial percentage of exports of natural resource over GDP might impair trade terms, cause unnecessary instability, and lead to low growth in productivity. Cadot et al (2013) provide three supporting grounds for this idea: (i) when the relative price of basic items falls, nations that rely heavily on commodities suffer from decreasing exports; (ii) due to unstable trade terms, the preponderance of primary items in the export basket is a component of growth-constraining instability; and (iii) focusing on basic commodities reduces productivity since primary commodities are typically laggards (Trinh and Thuy, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%